A BASE NACIONAL COMUM CURRICULAR (BNCC) E AS ORIENTAÇÕES CURRICULARES PARA A REDE DE ENSINO MUNICIPAL: O caso do Município de Santa Inês/MA - ABREU, Nayanna Judithe Vieira (2024)
This research is part of the Research Line: Educational Institutions, Curriculum, Teacher Training, and Work of the Graduate Program in Education. It focuses on the period between 2016 and 2019, marked by discussions on the National Common Curricular Base (BNCC) and its implementation process in the municipal education network of Santa Inês, in the State of Maranhão. Approved in December 2017, the BNCC aims to standardize basic education curricula and become a reality in all Brazilian schools. However, its approval occurred amidst conflicts and contradictions that excluded the participation of education professionals and disregarded key research institutions in the curriculum field, imposing changes hastily and imperatively. This study is guided by the following questions: How was the BNCC implementation process conducted in the municipal education network of Santa Inês? What changes did the BNCC implementation introduce to the school curricula in this network? This is a qualitative, bibliographical, and documentary research that aims to understand the implementation process of the BNCC and the DCTMA within the Municipal Department of Education of Santa Inês (SEMED), based on the municipality’s curricular guidelines. It highlights documentary evidence found in a municipal school belonging to Group 1. The study examines the legal and political history within the broader educational policy context, revealing a scenario of disputes from historical perspectives until the document’s approval. The BNCC fostered the implementation of these proposals, culminating in the materialization of the DCTMA in the state of Maranhão. The research is anchored in critical discussions on curriculum and the BNCC, drawing from scholars such as Freitas, Luís Carlos (2000); Freitas, Helena (1999); Gatti (2005); Saviani (2008; 2009; 2020); Oliveira (2018). The theoretical frameworks that address critical questions about the curriculum and the BNCC are based on Lopes (2018), Sacristán (2002; 2013), Arroyo (2013), Alves (2021), Aguiar (2011), Silva (2005), and Apple (2002). We argue that the primary curricular changes were shaped by institutional structures, their principles, and values, often diverging from the lived experiences of teachers. While the BNCC and DCTMA followed common implementation steps, this does not exempt schools from developing their own curriculum. The research employs the state-ofthe-art technique and a semi-structured script to collect data from the municipal network. Bardin’s (2016) content analysis technique is used, revealing that SEMED implemented the documents through the learning pact. Documentary evidence from a municipal school indicated strict adherence to the prescribed guidelines. However, despite efforts surrounding the BNCC and DCTMA, the local proposal remains unfinished.